Financial Challenges and Practices of Business Administration Students of a State University in Dumaguete City - Polinar, Mark Anthony N.; Zamora, Mary Jane; Delantar, Alexander Franco A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The study looked into the various significant financial challenges faced by business administration students of one of Dumaguete City's state colleges. Corollary to this objective, their current financial practices were also examined. Information from 308 respondents was gathered using a quantitative research method using Cochran’s approach and convenience sampling technique was used in the study. A self-administered questionnaire was used. And several published research articles influenced the development of the instrument. The data was evaluated using weighted mean and ranking. The findings revealed that the two most common financial challenges students had grappled with throughout their moderately difficult college years were obtaining a part-time job to supplement their parent-financed school allowance and not being able to purchase internet data to attend online classes. One of the students' major financial practices is to save as much money as possible, markedly considered as highly practiced in the study. Business administration students were moderately challenged by the recognized elements of financial challenges while being slightly practiced as described under Financial Challenges. Students are good at saving money and not buying things (that may pose a financial risk), in addition to working part-time. Further, the study suggested that the school administration conceive and implement a comprehensive financial education, elevate the level of students’ financial quotient by embedding financial courses in the curricula of programs, and consistently provide a series of seminars and workshops on the subject. Conducting pre-program and mid-program surveys may also determine the effectiveness of the program.